2012
DOI: 10.1080/13569775.2012.651275
|View full text |Cite
|
Sign up to set email alerts
|

The 2011 presidential election in Peru: a thorny moral and political dilemma

Abstract: The 2011 presidential elections in Peru was the third one held in the post-Fujimori era. A perusal of the campaign's political dynamics reveals pervasive anti-democratic behaviours, attitudes and rhetoric on the part of key political actors, showcasing the degree to which Peru remains an unconsolidated, precarious democracy. The second round presented a moral and political dilemma insofar as two unsavoury candidates of highly dubious democratic credentials vied for the presidency: Ollanta Humala, a former army… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In 2011, Ollanta Humala launched another presidential campaign that criticized the neoliberal economic model in the country and even proposed not to sign the MTA with the EU. His victory in the second election round against Keiko Fujimori, the daughter of Alberto Fujimori, showed that Humala had managed to strike a more moderate tone in his second campaign (Sánchez-Sibony 2011), but it also reflected an increasing instability of the neoliberal hegemony among the Peruvian population. During the first years of Humala’s presidency, some domestic brokers of the antineoliberal movement, like the economist Germán Alarco Tosoni and the labor expert Enrique Fernández-Maldonado, managed to attain positions in the Humala government.…”
Section: Peru: Discursive Influence Through the Eu During The Impleme...mentioning
confidence: 99%
“…In 2011, Ollanta Humala launched another presidential campaign that criticized the neoliberal economic model in the country and even proposed not to sign the MTA with the EU. His victory in the second election round against Keiko Fujimori, the daughter of Alberto Fujimori, showed that Humala had managed to strike a more moderate tone in his second campaign (Sánchez-Sibony 2011), but it also reflected an increasing instability of the neoliberal hegemony among the Peruvian population. During the first years of Humala’s presidency, some domestic brokers of the antineoliberal movement, like the economist Germán Alarco Tosoni and the labor expert Enrique Fernández-Maldonado, managed to attain positions in the Humala government.…”
Section: Peru: Discursive Influence Through the Eu During The Impleme...mentioning
confidence: 99%
“…He won the April/ May presidential elections, but the congress threatened him with the impeachment; thus, Fujimori resigned in November 2000 (Cameron & Mauceri, 1997;Mauceri, 1997;Stokes, 1997;Levitsky, 1999;Schmidt, 2000;Arce, 2003Arce, & 2005Kelly, 2003;Levitsky & Cameron, 2003;Carrión, 2006). (Weyland, 2002;Barr, 2003;Wise, 2003;Taylor, 2005;Mc Clintock, 2006;Arce, 2008;Burron, 2012;Levitt, 2012;Sanchez-Sibony, 2012;Vergara & Encinas, 2016;Vergara & Watanabe, 2016;Avilés & Rey Rosas, 2017;Durand, 2017;Tanaka & Morel, 2018).…”
Section: Fujimori: From Liberal (1990/2) To Conservative (1993/8) To ...mentioning
confidence: 99%
“…In this context, it is important to understand the political phenomena witnessed in the country, such as the leadership and popularity of Ms Fujimori, despite her being the daughter of ex-president Alberto Fujimori, who executed a self-coup, fled the country and served 11 years in prison for human rights abuses (Sánchez-Sibony, 2012). Another political phenomenon was the victory of Mr Pedro Pablo Kuczynski (PPK) in the most recent presidential elections in 2016.…”
Section: Introductionmentioning
confidence: 99%